Analysis of the Formulation of Health Laws in the Perspective of Media Coverage - Diyanti*, Dwi; Josias Simon Runturambi, Arthur (Universitas Syiah Kuala, 2024)
The drafting of the Health Law using the omnibus law method not only received pros and cons from various parties in the field but also spread to the world of digital media. This article aims to see differences in trends in reporting related to the drafting of the Health Law in the media. The qualitative method with a theoretical approach where media is the center of study (media-centric), which can be a driver of social change (socio-centric), becomes a perspective in analyzing the data found. The reporting trend in the mass media, where neutral sentiment is only 10%, shows that the space and time given to each party are not proportionally balanced, thus encouraging the publik to shift to the media to express views and opinions. Although this social media does not meet journalistic rules, it can offer digitization, convergence, interaction, and development of networks, which are considered more effective in communicating a publik interest.